A Case of an Extremely Low Birth Weight Infant with Morganella morganii Bacteremia and Peritonitis - Betty Pham; Anne Denslow; Michel Mikhael; Jina Lim (Thieme Medical Publishers, Inc., 2021)
We describe a case of late onset Morganella morganii sepsis in an extremely low birth weight male neonate born at 23 and 4/7 weeks gestational age to a 30-year-old primigravid mother due to preterm labor. The mother was otherwise healthy with an unremarkable prenatal course. She received steroids and ampicillin prior to delivery. While initial blood cultures were negative, at day of life 4, the neonate developed signs of sepsis with leukocytosis and bandemia, and subsequent blood culture demonstrated growth of M. morganii. The patient then had spontaneous intestinal perforation on day of life 8 with peritoneal cultures growing M. morganii. The infant responded to standard therapy and survived to discharge, with few mild developmental delays upon outpatient follow-up. While M. morganii has been demonstrated in the neonatal population, it generally causes early onset sepsis and is associated with high mortality in preterm neonates. Here, we present this case of late onset neonatal sepsis with M. morganii complicated by spontaneous intestinal perforation, with survival in a 23 weeks gestation infant.